2018
DOI: 10.3390/rs10091482
|View full text |Cite
|
Sign up to set email alerts
|

Surface Moisture and Vegetation Cover Analysis for Drought Monitoring in the Southern Kruger National Park Using Sentinel-1, Sentinel-2, and Landsat-8

Abstract: During the southern summer season of 2015 and 2016, South Africa experienced one of the most severe meteorological droughts since the start of climate recording, due to an exceptionally strong El Niño event. To investigate spatiotemporal dynamics of surface moisture and vegetation structure, data from ESA’s Copernicus Sentinel-1/-2 and NASA’s Landsat-8 for the period between March 2015 and November 2017 were utilized. In combination, these radar and optical satellite systems provide promising data with high sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 64 publications
(78 reference statements)
1
42
0
1
Order By: Relevance
“…In this study, it was found from the study that in 2015, it was the time when drought was at most level equal to 91.54 or equal to 44975.23 km 2 . When the results of the study were used to compare with other similar researches such as research on "Application of remote sensing technology for drought monitoring in Mahasarakham Province, Thailand" by Laosuwan et al, (2016), research on "Drought Detection by Application of Remote Sensing Technology and Vegetation Phenology" by Uttaruk & Laosuwan, (2017), research on "Remote Sensing Based Drought Monitoring In The Middle-Part of Northeast Region of Thailand" by Rotjanakusol & Laosuwan, (2018), research on "Surface Moisture and Vegetation Cover Analysis for Drought Monitoring in the Southern Kruger National Park Using Sentinel-1, Sentinel-2, and Landsat-8" by Urban et al, (2018), it was found that 4 researches had the analysis results in the same direction with that of this study. The result of this study can be used as criteria in making reasonable decision on the Chi watershed area affected by drought, and also can be used to assess the drought area rapidly and reliably.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found from the study that in 2015, it was the time when drought was at most level equal to 91.54 or equal to 44975.23 km 2 . When the results of the study were used to compare with other similar researches such as research on "Application of remote sensing technology for drought monitoring in Mahasarakham Province, Thailand" by Laosuwan et al, (2016), research on "Drought Detection by Application of Remote Sensing Technology and Vegetation Phenology" by Uttaruk & Laosuwan, (2017), research on "Remote Sensing Based Drought Monitoring In The Middle-Part of Northeast Region of Thailand" by Rotjanakusol & Laosuwan, (2018), research on "Surface Moisture and Vegetation Cover Analysis for Drought Monitoring in the Southern Kruger National Park Using Sentinel-1, Sentinel-2, and Landsat-8" by Urban et al, (2018), it was found that 4 researches had the analysis results in the same direction with that of this study. The result of this study can be used as criteria in making reasonable decision on the Chi watershed area affected by drought, and also can be used to assess the drought area rapidly and reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Further emphasis is on computational approaches taking advantage of and adding value to publicly available satellite imagery such as data from NASA's Landsat missions and ESA's Sentinel (Copernicus) programme (e.g. Cremer et al 2018;Urban et al 2018). The resulting methods are used to derive land surface parameters related to the status and dynamics of South Africa's terrestrial ecosystems (e.g.…”
Section: Leveraging Earth Observation Data To Support Ecosystem Monitmentioning
confidence: 99%
“…fuel biomass, woody cover, vegetation heights, land use) to implement environmental and socio-ecological mapping, monitoring, and management with direct societal benefits (e.g. Urbazaev et al 2015;Odipo et al 2016;Urban et al 2018). An example application is the spatiotemporal characterisation of fuel biomass and fuel moisture content for improved fire management in the Kruger National Park.…”
Section: Leveraging Earth Observation Data To Support Ecosystem Monitmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many applications for monitoring the earth's phenomena using optical remote sensing images e.g., agriculture (He et al, 2018), forestry (Townshend et al, 2012;Zhu et al, 2012b), marine (Roelfsema et al, 2013), land use land cover analysis (Nutini et al, 2013;Varade et al, 2018), and disaster: floods (Arnesen et al, 2013;Mason et al, 2014;Schlaffer et al, 2015), droughts (Urban et al, 2018), earthquakes (Fan et al, 2019). Unfortunately, there is a serious issue related to cloud coverage on the optical remote sensing images.…”
Section: Introductionmentioning
confidence: 99%